The Impact of Economic Growth, Education Level, and Inflation Rate on Income Inequality in Malaysia - Regina Lee, Junup; Nur Nadhira, Baharuddin; Joanne Shaza, Janang (Human Resource Management Academic Research Society (HRMARS), 2023)
Purpose: The goal of this study is to look at the determinants that contribute to income inequality in Malaysia.